2018
DOI: 10.1088/1748-605x/aaaa2d
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer-based membranes associated with osteogenic growth peptide for guided bone regeneration

Abstract: Barrier membranes for guided bone regeneration (GBR) mainly promote mechanical maintenance of bone defect space and induce osteopromotion. Additionally, biopolymer-based membranes may provide greater bioactivity and biocompatibility due to their similarity to extracellular matrix (ECM). In this study, biopolymers-based membranes from bacterial cellulose (BC) and collagen (COL) associated with osteogenic growth peptide (OGP(10-14)) were evaluated to determine in vitro osteoinductive potential in early osteogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
7
0
2
Order By: Relevance
“…Guided bone regeneration membrane tubes can be used as a support material in bone tissue engineering, the combination of growth factors and membrane tubes can enhance proliferation, chemotaxis, and differentiation of osteogenic cells. 23,24 With good biocompatibility and mechanical properties, the novel n-CDHA-MAC membrane tube has good potential to be used in the bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Guided bone regeneration membrane tubes can be used as a support material in bone tissue engineering, the combination of growth factors and membrane tubes can enhance proliferation, chemotaxis, and differentiation of osteogenic cells. 23,24 With good biocompatibility and mechanical properties, the novel n-CDHA-MAC membrane tube has good potential to be used in the bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…OGP has been incorporated into regenerative membranes used in the GTRT. For instance, it has been shown that membranes based on biopolymers combined with OGP-(10-14) stimulate the proliferation and activity of osteoblasts in vitro, as well as the repair of bone tissue in vivo (Saska et al, 2018). Both, in vitro and in vivo experiments showed that the material is beneficial for cell adhesion, has good biocompatibility, enhances the expressions of osteogenic-related genes, and accelerates bone regeneration.…”
Section: Osteogenic Growth Peptidementioning
confidence: 99%
“…In view of these requirements, several biomaterials have been highlighted in reconstructive surgery and regenerative medicine due to the ability to mimic tissue microstructure, allowing reactions inherent to the extracellular matrix and in the regulation of cellular phenotypes. Among these biomaterials, polymeric matrices, natural or synthetic, have shown satisfactory preclinical and clinical results [6].…”
Section: Introductionmentioning
confidence: 99%